2016
DOI: 10.1016/j.jfs.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The new financial regulation in Basel III and monetary policy: A macroprudential approach

Abstract: The aim of this paper is to study the interaction between the Basel banking regulations and monetary policy. In order to do that, we use a dynamic stochastic general equilibrium (DSGE) model with a housing market, banks, borrowers, and savers. First, we …nd that higher capital requirement ratios (CRR), implied by the Basel regulations, has distributional e¤ects among agents: an increase in the welfare of borrowers at the expense of savers and banks. However, if we let monetary policy to react optimally to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…6 Ebrahimi Kahou and Lehar (2017) provide a comprehensive review on macroprudential policy. One strand, which we will not be able to discuss in detail, consists of theoretical contributions based on the New Keynesian DSGE models with financial frictions to model the interaction between monetary and macroprudential policy (see, e.g., Angelini et al 2014;Rubio & Carrasco-Gallego 2015;Cesa-Bianchi & Rebucci 2016;Rubio & Carrasco-Gallego 2016;Chen et al 2017). 5 distribution and dynamic provisioning.…”
mentioning
confidence: 99%
“…6 Ebrahimi Kahou and Lehar (2017) provide a comprehensive review on macroprudential policy. One strand, which we will not be able to discuss in detail, consists of theoretical contributions based on the New Keynesian DSGE models with financial frictions to model the interaction between monetary and macroprudential policy (see, e.g., Angelini et al 2014;Rubio & Carrasco-Gallego 2015;Cesa-Bianchi & Rebucci 2016;Rubio & Carrasco-Gallego 2016;Chen et al 2017). 5 distribution and dynamic provisioning.…”
mentioning
confidence: 99%
“…2. This work includes Covas and Fujita, 2010;Darracq Pariès, Kok Sørensen, and Rodriguez-Palenzuela, 2011;Angeloni and Faia, 2013;Repullo, 2013;Angelini, Neri, and Panetta, 2014;Rubio and Carrasco-Gallego, 2016;Aliaga-Díaz, Olivero, and Powell, 2017;Hollander, 2017;Malherbe, 2017;and Davydiuk, 2017. Haubrich and DeKoning, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Rubio and Carrasco-Gallego studied the macroprudential effect of counter-cyclical capital under Basels I, II, and III. e research showed that the welfare effect of each department was different under various capital ratio requirements and corresponding monetary policy rules were needed to achieve the optimal control effect [15].…”
Section: Literature Reviewmentioning
confidence: 99%